Mechanisms of the Deleterious Effects of Tamoxifen on Mitochondrial Respiration Rate and Phosphorylation Efficiency - Cardoso, Carla M. P. (2001)
Tamoxifen (TAM), the widely prescribed drug in the prevention and therapy of breast cancer, is a well-known modulator of estrogen receptor (ER) that also inhibits the proliferation of different cell types that lack the ER. However, the ER-independent action mechanisms of TAM and its side effects have not been yet clarified. Mitochondria are essential in supporting the energy-dependent regulation of cell functions. Changes in mitochondria result in bioenergetic deficits leading to the loss of vital functions to cell survival. Therefore, this study describes the effects of TAM on mitochondrial bioenergetics, contributing to a better understanding of the biochemical mechanisms underlying the multiple antiproliferative and toxic effects of this drug. TAM at concentrations above 20 nmol/mg protein, preincubated with isolated rat liver mitochondria at 25°C for 3 min, significantly depresses, in a dose-dependent manner, the phosphorylation efficiency of mitochondria as inferred from the decrease in the respiratory control and ADP/O ratios, the perturbations in mitochondrial transmembrane potential ([Delta][Psi]), the fluctuations associated with mitochondrial energization, and the phosphorylative cycle induced by ADP. Furthermore, TAM at up to 40 nmol/mg protein stimulates the rate of state 4 respiration and at higher concentrations it strongly inhibits state 3 and uncouples the mitochondrial respiration. The stimulation of state 4 respiration parallels the decrease of [Delta][Psi] as a consequence of proton permeability. The TAM-stimulatory action of ATPase is also observed in intact mitochondria, suggesting that TAM promotes extensive permeability to protons due to destructive effects in the structural integrity of the mitochondrial inner membrane. These multiple effects of TAM on mitochondrial bioenergetic functions, causing changes in the respiration, phosphorylation efficiency, and membrane structure, may explain the cell death induced by this drug in different cell types, its anticancer activity in ER-negative cells, and its side effects.